Glucose Response to an Oral Glucose Tolerance Test Predicts Weight Change in Non-diabetic Subjects - Pannacciulli, Nicola (2007)
OBJECTIVE: Glucose exerts a dual action in the regulation of energy balance, consisting of inhibition of energy intake and stimulation of energy expenditure. Whether blood glucose affects long-term regulation of body weight in humans remains to be established. We sought to test the hypothesis that the post-challenge glucose response is a predictor of weight change. RESEARCH METHODS AND PROCEDURES: We performed a prospective analysis of the impact of glucose response to an oral glucose tolerance test (OGTT) and a mixed-meal test (MT) on subsequent changes in body weight (BW) on 253 Pima Indians (166 men and 87 women) with normal glucose regulation at baseline and follow-up (follow-up: 7 ± 4 years). Main outcome measures included BW change (total, percent, and annual), plasma glucose and insulin concentrations during OGTT and MT [total and incremental areas under the curve (AUCs)], resting metabolic rate (RMR; indirect calorimetry), and insulin action (euglycemic-hyperinsulinemic clamp). RESULTS: Total and incremental glucose AUCs during the OGTT (but not the MT) were negatively associated with BW change (total, percent, and annual), both before and after adjusting for sex, age, initial BW, follow-up time, insulin action, RMR, fasting plasma glucose and insulin concentrations, and insulin response. Total and incremental glucose AUCs during the OGTT were independent determinants of final BW with age, initial BW, follow-up time, fasting plasma insulin concentrations, and RMR. DISCUSSION: Higher post-challenge glucose response protects against BW gain in subjects with normal glucose regulation. We propose that this action may be because of the effect of glucose on food intake and/or thermogenesis.